Magnetically Chitosan-Silica-Based Biosorbent as Efficient Removal of Au(III) in Artificial Wastewater - Pradipta, Adya Rizky; Putri, Regita Andriani Wiana; Khairani, Inna Yusnila; Hasnowo, Lutfi Aditya (Indonesian Scholar Society, 2024)
The synthesis of chitosan-modified silica-coated iron oxide magnetic material (Fe3O4/SiO2/Chitosan) via the sol-gel process addresses the need for enhanced stability and functionality in various applications. Coating iron oxide magnetic material with chitosan-modified silica is a common strategy to improve biocompatibility and performance. This study investigates the synthesis of Fe3O4/SiO2/Chitosan using sodium silicate as the silica precursor. The synthesis involved sonication of Fe3O4 and sodium silicate for 5 min, followed by adding chitosan in 4% acetic acid with continuous stirring. The mass ratio of Fe3O4:SiO2 was fixed at 0.5:0.73, with varying chitosan masses (0.025, 0.050, and 0.075 g). Characterization techniques used included Fourier-Transform Infrared Spectroscopy (FTIR), X-ray powder Diffraction (XRD), and Thermogravimetric analysis (TGA). The product with the highest mass yield was further analyzed. The variation in the amount of chitosan in the conducted research aimed to determine the optimum chitosan mass that could still bind to the silica framework. Magnetite was confirmed as the primary composition, with the addition of chitosan and silica functional groups observed through vibration absorption characteristics. Thermogravimetric analysis showed differences in decomposition patterns between samples. The optimal chitosan content for characterization was determined at 0.050 g. Future applications might include enhanced adsorption processes owing to the optimized structure and composition of Fe3O4/SiO2/Chitosan nanoparticles.